Pelatihan Pengembangan Media Augmented Reality sebagai Strategi Peningkatan Kompetensi Digital Guru SMP di Kecamatan Salahutu, Maluku Tengah: Training on the Development of Augmented Reality-Based Learning Media as a Strategy to Enhance the Digital Competence of Junior High School Teachers in Salahutu District, Central Maluku - Mery Pattipeilohy; Yeslia Utubira; Lita Lokollo; Muhammad Tarmizi Kubangun (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This Community Service (PkM) activity aims to improve the digital competence of junior high school teachers through training on developing Augmented Reality (AR)-based learning media in Salahutu District, Central Maluku Regency. The activity was carried out in a participatory manner through three stages, namely preparation, implementation, and follow-up, involving 28 teachers as participants. The training process began with a pre-test and ended with a post-test to measure improvements in competency. The training used a hands-on approach that allowed participants to gain direct experience designing AR-based learning media and produce products ready for use in the classroom. The results of the statistical analysis showed that the average pre-test score was 76.21 with a standard deviation of 18.72, and the average post-test score was 84.07 with a standard deviation of 16.71. In addition, the n-gain calculation of 0.35 falls within the moderate category, indicating an increase in teachers' digital competence, particularly in conceptual knowledge, technological understanding, and practical skills in AR media development. The questionnaire response results showed an acceptance rate of 93.69%, indicating that AR technology was perceived as relevant, easy to use, and pedagogically valuable in visualizing abstract concepts. The formation of a community of AR-developing teachers became a strategy for the program's sustainability. Overall, this training proved effective in strengthening teachers' digital competencies and encouraging a more interactive, contextual transformation in learning across the archipelago region.